EFFECT OF SOAKING IN KASGOT (MAGGOT WASTE) FERTILIZER ON THE GROWTH AND CARAGENAN CONTENT OF SEAWEEDS Kappaphycus alvarezii - Ardi Eko Mulyawan; Andi Megawati; Frida Alifia (Universitas Mataram, 2025)
Kappaphycus alvarezii seaweed produces carrageenan; its growth and development are highly dependent on the quality of the waters and nutrients such as nitrate, phosphate, and potassium. The planting method that cultivators often carry out is to take it directly from the seaweed that is being harvested. This pattern makes the growth of seaweed less than optimal. One solution is to fertilize. One type of fertilizer that can be used is natural fertilizer, such as kasgot fertilizer. This study aims to determine the combination of soaking time and concentration of kasgot fertilizer that effectively increases the growth and carrageenan content of Kappaphycus alvarezii. This research method uses the treatment of the duration of kasgot fertilizer immersion for 2 hours, 4 hours, 6 hours and without immersion (control) and the concentration of kasgot fertilizer of 2 grams, 4 grams, 6 grams, and without kasgot fertilizer (control), repeated 3 times. The results show that the kasgot fertilizer immersion treatment can increase weight, growth rate, and carrageenan value. The higher the dose given, the higher the weight, growth rate, and carrageenan value, although in statistical tests, it was found that the immersion treatment did not significantly affect weight or growth rate. Water quality during the study (temperature, salinity, pH, and depth) was still within the standards for cultivating K. alvarezii seaweed. Further research is needed on using kasgot fertilizer in cultivating other types of seaweed or using different doses.